Deep Into the Chibougamau Area, Abitibi Greenstone Belt: Structure of a Neoarchean Crust Revealed by Seismic Reflection Profiling. Issue 7 (22nd July 2020) - Mathieu, Lucie; Snyder, David B.; Bedeaux, Pierre; Cheraghi, Saeid; Lafrance, Bruno; Thurston, Phil; Sherlock, Ross
Abstract: Copper‐gold magmatic‐hydrothermal systems dominate in the Chibougamau area of the Neoarchean Abitibi subprovince (greenstone belt) of the Superior Province (craton), whereas orogenic gold mineralization is more common in the rest of the Abitibi. Understanding differences in metal endowment within the Abitibi greenstone belt requires insights into the geodynamic evolution of the Chibougamau area. This was addressed by imaging the crust using seismic reflection profiling acquired as part of the Metal Earth project. Seismic reflection sections display shallowly south‐dipping reflectors located within the upper crust (e.g., a possible deep continuation of the Barlow fault) and a northward‐dipping midcrust imbricated with older crust (Opatica subprovince) to the north. Multiple reflectors characterize the upper part of the midcrust, interpreted as faults superimposed on a major lithological boundary. These structures likely formed during terrane accretion prior to craton stabilization. Combining the new seismic data with known stratigraphic, structural, and magmatic records, we propose that the study area was initially a normal (i.e., thick) Archean oceanic crust that formed at or before 2.80 Ga and that evolved through terrane imbrication at 2.73–2.70 Ga. Shortening caused rapid burial, devolatilization, and partial melting of hydrated mafic rocks to produce tonalite magmas that may have mixed with mantle‐derived melts to produce the diorite‐tonalite suite associated with observed Cu‐Au magmatic‐hydrothermal mineralization. Key Points: A seismic reflection survey of the Chibougamau area, Abitibi greenstone belt, is performed by the Metal Earth project The Metal Earth and Lithoprobe seismic surveys reveal that the northern part of the Abitibi greenstone belt has a consistent architecture The Chibougamau area is an Archean oceanic crust evolved through terrane imbrication and not through plume activity and subduction processes